Poor Skeletal Robustness on Lower Extremities and Weak Lean Mass Development on Upper Arm and Calf: Normal Weight Obesity in Middle-School-Aged Children (9 to 12) - Musálek, Martin; Pařízková, Jana; Godina, Elena; Bondareva, Elvira; Kokštejn, Jakub; Jírovec, Jan; Vokounová, Šárka (Frontiers in Pediatrics, 2018)
Background: Normal weight obesity in children has been associated with excessive body fat, lower bone density and decreased total lean mass. However, no studies have been done into whether normal weight obese children differ in skeletal robustness or lean mass development on the extremities from normal weight non-obese, overweight, and obese peers although these are important indicators of healthy development of children. Methods: Body height, body weight, BMI, four skinfolds and two limb circumferences were assessed. We calculated total body fat using Slaughter’s equations, the Frame index for skeletal robustness and muscle area for the upper arm and calf using Rolland-Cachera equations. Using national references of BMI and measured skinfolds, three subgroups of children (9-12 years) consisting of 210 middle-school-aged children (M-age = 11.01 ±1.05)—110 girls and 100 boys—were selected: A) overweight obese (OWOB) (n = 72); B) normal weight obese (NWO) (n = 69); and, C) normal weight non-obese (NWNO) (n = 69). All values, regardless of age or sex, were converted to Z-scores. Results: NWO children had significantly poorer skeletal robustness on lower extremities and poorer muscle area on the upper arm and calf compared to NWNO counterparts with significantly higher evidence in boys – skeletal robustness NWO boys: Z-score= -0.85; NWO girls: Z-score = -0.43; lean mass on the calf: NWO boys Z-score= -1.34; NWO girls: Z-score = -0.85. The highest skeletal robustness—but not muscle area on the calf—was detected in OWOB children. Conclusions: Further research should focus on whether this poor skeletal and lean mass development: 1) is a consequence of insufficient physical activity regimes; 2) affects physical fitness of NWO children and could contribute to a higher prevalence of health problems in them. We have highlighted the importance of the development of a simple identification of NWO children to be used by pediatricians.